Pengaruh Faktor Personal Resources, Job Resources serta Organizational Internal & External Environment terhadap Employee Intentional Digital Readiness - Marpaung, Veronika Br; Savitri, Elok (Dinasti Research, 2026)
This study aims to analyze the roles of personal resources, job resources, and the internal and external organizational environment in influencing employee intentional digital readiness, mediated by perceived usefulness and perceived ease of use through the moderation of leadership support, in the manufacturing industry in the Karawang, Cikarang, and Bekasi regions. Involving 533 active employees working in manufacturing companies that have adopted digitalization, this study uses quantitative methods by distributing questionnaires to collect data. Data analysis was conducted using structural equation modeling (SEM) techniques with the LISREL application to determine the relationships between the variables studied. The results show that both personal resources and job resources significantly contribute to employee intentional digital readiness. Additionally, the organizational internal environment does not significantly contribute to increasing employee digital readiness, while the external environment indicates that partner support has a significant impact on employee readiness. Leadership support plays an important moderating role, strengthening the relationship between perceived usefulness and perceived ease of use on employee intentional digital readiness. These findings provide valuable insights for manufacturing industry managers in designing strategies to enhance employee digital readiness through the development of resources and effective leadership support.